2018
DOI: 10.1016/j.bandc.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diabetes on prefrontal cortex activation patterns during active walking in older adults

Abstract: Background Gait alterations were documented in diabetic patients. However, the effect of diabetes on cortical control of gait has not been reported. We evaluated the effect of diabetes on prefrontal cortex (PFC) Oxygenated Hemoglobin (HbO2) levels during active walking in older adults. Methods Of the total sample (n=315; mean age=76.84±6.71ys; %female=56.5) 43 participants (13.7%) had diabetes. The experimental paradigm consisted of two single tasks: Normal-Walk (NW); and Cognitive Interference (Alpha); and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 63 publications
2
39
0
Order By: Relevance
“…Also in participants from the CCMA study, higher levels of self-perceived stress and fatigue were associated with attenuation of brain activation patterns (lower increase in O 2 Hb levels from ST to DT walking) (Holtzer et al, 2017a,b). Participants with diabetes from the same study showed lower PFC activation during DT, compared to non-diabetics (Holtzer et al, 2018a), while obese cognitively healthy older adults from a different study showed higher activation, especially during a precision walking task, compared to non-obese counterparts (Osofundiya et al, 2016). When combining fNIRS with cerebral microstructural white matter integrity assessment, using MRI with Diffusion Tensor Imaging (DTI), altered white matter integrity was associated to higher O 2 Hb levels during DT walk compared to normal walk in the CCMA study (Lucas et al, 2018).…”
Section: Association Between Activation and Clinical Variablesmentioning
confidence: 83%
See 1 more Smart Citation
“…Also in participants from the CCMA study, higher levels of self-perceived stress and fatigue were associated with attenuation of brain activation patterns (lower increase in O 2 Hb levels from ST to DT walking) (Holtzer et al, 2017a,b). Participants with diabetes from the same study showed lower PFC activation during DT, compared to non-diabetics (Holtzer et al, 2018a), while obese cognitively healthy older adults from a different study showed higher activation, especially during a precision walking task, compared to non-obese counterparts (Osofundiya et al, 2016). When combining fNIRS with cerebral microstructural white matter integrity assessment, using MRI with Diffusion Tensor Imaging (DTI), altered white matter integrity was associated to higher O 2 Hb levels during DT walk compared to normal walk in the CCMA study (Lucas et al, 2018).…”
Section: Association Between Activation and Clinical Variablesmentioning
confidence: 83%
“…O 2 Hb increase was highest in the post-stroke group, followed by older and young adults. * Holtzer (Brain Cogn., 2018), USA (Holtzer et al, 2018a) N = 315 Healthy old (76.8 ± 6.7). Prefrontal.…”
Section: Hawkinsmentioning
confidence: 99%
“…We used HbO 2 and not Hb as a surrogate for neural activity in the PFC because the former is more reliable and sensitive to gait-related changes in brain activation patterns [46,47]. We administered proximal 10-s baselines immediately before each experimental condition to quantify relative changes in HbO 2 for each task [19,20,22,23,48]. A central "hub" computer with E-Prime 2.0 software synchronized the acquisition of Gait and fNIRS events [19][20][21][22][23][24].…”
Section: Preprocessing and Hemodynamic Signal Extractionmentioning
confidence: 99%
“…In recent years, functional Near-Infrared Spectroscopy (fNIRS) has been used to investigate changes in the hemodynamic response during active walking in humans (for reviews, see [17,18]). Specifically, studies revealed that, in older adults, fNIRS-derived Oxygenated Hemoglobin (HbO 2 ) in the Prefrontal Cortex (PFC) was increased in Dual-Task-Walk (DTW) compared to Single-Task-Walk (STW) conditions due to the greater attention and executive demands imposed by DTW [19][20][21][22][23]. Moreover, repeated training trials during one experimental session resulted in improved behavioral performance and brain efficiency, the latter operationalized using fNIRS-derived HbO 2 , in DTW but not STW conditions [24].…”
Section: Introductionmentioning
confidence: 99%
“…Third, the walking function might reflect metabolism in the brain. Holtzer and colleagues suggested that elderly patients with diabetes mellitus exhibit altered frontal lobe function during walking and are at a risk of falling [41]. Fourth, it is possible that hypoglycemia caused by sulphonylurea and insulin is linked to abnormalities in brain metabolism and a reduced walking speed.…”
Section: Why Is Reduced Walking Speed Associated With Mci?mentioning
confidence: 99%